Hilfsmittel und Verfahren für zellbasiertes high content imaging - Gilbert, Daniel; Friedrich, Oliver; Lesko, Christian; Hartmann, Kristin (BioSpektrum, 2021)
Cell-based high content imaging has become a versatile and powerful method for studying e. g. cellular viability, morphology or physiology. However, high content imaging and its various applications require complex as well as expensive hardware and consumables, limiting its utility and usability. To broaden the applicability of cell-based high content imaging, we have developed tools and assaying techniques being exemplary portrayed in this article.
CRIS-Team Scopus Importer:2021-04-02